On the occurrence of parasites in free-ranging callitrichids - Santos, Francisco G. de Araújo; Bicca-Marques, Júlio César; Calegaro-Marques, Cláudia; de Farias, Elvira M. P.; Azevedo, Maria Aparecida de O. (Neotropical Primates, 1995)
No abstract